Moderation Study The Influence of Managerial Competence, Internal Control Systems, Community Participation, and Siskeudes on Accountability in Village Fund Management: A Study of Prosocial Behavior as a Moderating Variable - Arbianti Arbianti; Enni Savtri; M. Rasuli (International Journal of Economics Development Research (IJEDR), 2024)
This research aims to analyze and test the influence of Manager Competence, Internal Control System, Community Participation, and Siskeudes on Village Fund Management Accountability with Prosocial Behavior as a Moderating Variable (Study of Village Government in Kampar Regency). The population in this study was all villages in Kampar Regency, totaling 242 villages. Sampling in this study used the Slovin formula, where according to this method the resulting sample was 151 villages. The sample was selected using the Proportional Stratified Random Sampling method or simple random sampling with respondents from village heads, heads of finance and BPD. Data analysis uses the data analysis method used in this research using the Smart PLS version 4.0 application.The results of the research show that there is an influence of manager competency, internal control system, community participation, siskeudes on accountability for village fund management, there is an influence of manager competency on accountability for village fund management with prosocial behavior as a moderating variable, there is an influence of internal control system on accountability for village fund management with prosocial behavior as a moderating variable, there is an influence of community participation on accountability in managing village funds with prosocial behavior as a moderating variable, there is an influence of siskeudes on accountability in managing village funds with prosocial behavior as a moderating variable